An emotion regulation skills training for adolescents and parents: perceptions and acceptability of methodological aspects - Holmqvist Larsson, Kristina; Zetterqvist, Maria (Frontiers in Psychiatry, 2024)
IntroductionDifficulties with emotion regulation are associated with the development and maintenance of psychiatric symptoms. Focusing on emotion regulation can be beneficial when treating symptoms and behavioral problems. Here we describe a seven-session transdiagnostic approach to regulating emotions, delivered jointly to adolescents and parents in a child and adolescent psychiatric outpatient setting, and we explore the perceptions and acceptability of the methodological aspects of the intervention.MethodsQuantitative and qualitative data were analyzed. Participants (n = 117) were adolescents and parents.ResultsParticipants reported positive attitudes toward the skills training and would recommend it to others. Three overarching themes were developed. “Treatment components” relates to the content of the skills training. Participants appreciated focusing on ER skills but had different perceptions of the content. “The learning climate” contains process-related experiences, such as the skills trainers’ approach and the timing of the intervention. Participants preferred when skills trainers used self-disclosure. “Pedagogical aspects”, describes the structure of the training with perceptions of group constellations, length of sessions and homework. Adolescents particularly requested variety in the pedagogy and found long sessions to be challenging.DiscussionRecommendations for therapeutic practices are discussed.